The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/0074-02760200443
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and morphogenesis of SARS-CoV-2 in Vero-E6 cells

Abstract: BACKGROUNDThe coronaviruses (CoVs) called the attention of the world for causing outbreaks of severe acute respiratory syndrome (SARS-CoV), in Asia in 2002-03, and respiratory disease in the Middle East (MERS-CoV), in 2012. In December 2019, yet again a new coronavirus (SARS-CoV-2) first identified in Wuhan, China, was associated with a severe respiratory infection, known today as COVID-19. This new virus quickly spread throughout China and 30 additional countries. As result, the World Health Organization (WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
5
12
1
1
Order By: Relevance
“…We observed that the entry of the SARS-CoV-2 into the host cell occurs most commonly by endocytosis, although the fusion of the virus envelope with the cell membrane has also been observed. This is consistent with our previous ultrastructural studies with SARS-CoV-2 [23] and others from literature with SARS-CoV and MERS-CoV which support both mechanisms [9,43,44].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed that the entry of the SARS-CoV-2 into the host cell occurs most commonly by endocytosis, although the fusion of the virus envelope with the cell membrane has also been observed. This is consistent with our previous ultrastructural studies with SARS-CoV-2 [23] and others from literature with SARS-CoV and MERS-CoV which support both mechanisms [9,43,44].…”
Section: Discussionsupporting
confidence: 93%
“…We believe that the role of filopodia in this in vitro model is associated with infection maximization. In vitro studies with Vero cells with SARS-CoV and SARS-CoV-2 corroborate our findings [23,31,32]. Enveloped viruses can spread by two different routes: the cell-free aqueous environment or by cell-to-cell contact [33][34][35].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been reported that SARS-CoV-2 infected Vero E6 cells produce many lopodia, and they are longer than those present in uninfected cells 16,17 . We observed these very long lopodia and followed their path.…”
Section: Inter-cellular Connections By Tunneling Nano Tubesmentioning
confidence: 97%
“…The lipid envelope of SARS-CoV-2 contains an envelope protein, a spike protein S, and a membrane protein. The nucleocapsid protein forms the virion core encased in the viral genome [ 17 ]. The S protein mediates viral binding to the host cell surface [ 28 ].…”
Section: Virion Structurementioning
confidence: 99%